"Capt. Willis Bemister (uncle)" - Rorke Family (1865)
Captain Willis Bemister. Capt. Willis Bemister (1819-1869), son of William Willis Bemister and Ann (Howell) Bemister, and brother of Mary Bemister Forward, William Bemister and Hon. John G. Bemister, was born at Carbonear in 1819. He married Mary Elizabeth Bartlett at Carbonear on 14 August 1844, and had seven children. He was captain of the ''Mary Ann'' and later ''Two Brothers''. Capt. Bemister died in New York, New York on 5 July 1869. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.